PENGEMBANGAN MEDIA PEMBELAJARAN MEMBACA SLOKA MENGGUNAKAN APLIKASI SPARKOL VIDEOSCRIBE - Ni Nyoman Sudiani (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Chanting slokas is one of the media to spread Hindu teachings, as did the sages. However, the problem that is often faced is that it is not easy to sing the sloka well. Many people have difficulty learning to read slokas, including STAH DN Jakarta students. Seeing this problem inspired researchers to conduct research and development of reading sloka media, namely by utilizing the Sparkol VideoScribe application.The research uses research and development methods, namely making audio-visual media, so that students can see the script and hear the strains of the song. The rhythm used is the Sruti rhythm, because the UDG (national sloka reading competition) uses the Sruti rhythm. Videos are also accompanied by up and down rhythms. The limited trial used the experimental method, namely the experimental class was treated with video and the control class was conventionally treated. The result of the research is that video reading sloka based on the VideoScribe application is very effective in helping students learn to read sloka independently. The video is equipped with text and sound, students can also be guided by the rise and fall of the rhythm. The conclusion of this study is that video reading sloka based on the VideoScribe application is very important to develop because it is proven to be able to help students learn to read sloka independently.